Training on The Use of KIT Science Laboratory Equipment for Teachers and Students to Support The Implementation of The Independent Curriculum - Rizky Nafaida; Ekariana S. Pandia; Ratih Permana Sari; Nursamsu Nursamsu (Unram Journal of Community Service, 2023)
The aim of the service is to train the skills of teachers and students in recognizing, designing and using the set of practical tools in the Integrated Science KIT based on the Independent Curriculum. To train teachers and students in strengthening basic science concepts according to the basic concepts related to the available science KIT. To train science KIT teachers and participants on the components of each existing Science KIT set/box and relate them to existing basic science concepts. to train teachers' skills in assembling or assembling science KIT tools. To train the skills of teachers and students in using the KIT Science tool. To train the skills of teachers and students in designing experiments according to the existing Science KIT. To train the skills of teachers and students in using the Science KIT set as a learning medium. To be an accompaniment to the use of Science KIT in learning. The method in PkM activities uses training methods. The results of PkM activities have a positive impact on teachers and students in the use of science practicum laboratory equipment at Muhammadiyah Langsa High School